Heat acclimation - Racinais, S.; Sawka, M.; Daanen, H.; Périard, J. D. (Heat stress in sport and exercise. Thermophysiology of health and performance, 2019)
Physical exercise under heat stress can impair performance through multiple physiological mechanisms including cardiovascular, central nervous system, and skeletal muscle metabolism factors. However, repeated heat exposure that increases whole-body temperature, stimulates profuse sweating, and stresses the cardiovascular system, leads to increases in blood volume, decreases in core and skin temperatures, and induces important molecular adaptations that stimulate physiological heat acclimation. These integrated physiological adaptations act to improve exercise capacity in the heat, as well as minimise the risk of exertional heat illness. Most physiological benefits are noticeable within a few days of daily heat exposure, but the full benefits take about 2 weeks or longer to improve exercise capacity in the heat.